POTENTIAL OF PLANT MATERIALS FOR THE MANAGEMENT OF COWPEA BRUCHID CALLOSOBRUCHUS ANALIS (COLEOPTERA: BRUCHIDAE) IN GRAM CICER ARIETINUM DURING STORAGE - Sarwar, M.; Ahmad, N.; Bux, M.; Tofique, M. (The Nucleus, 2012)
Present research was carried out to identify alternatives to synthetic insecticides to control cowpea weevil Callosobruchus analis (F.) population in gram seed (Cicer arietinum L.), during storage. The efficacies of three plant materials such as Nicotiana tabacum, Citrullus colocythis and Aloe vera were assessed to determine their insecticidal activities against survival of bruchid C. analis on seeds of gram varieties viz., CM-98 and Jubiha-1. These plant materials tested reduced weevil infestation and emergence as compared with untreated control seeds. Seeds treatment with A. vera followed by N. tabacum reduced maximum pest damage over C. colocythis, which proved least effective to control C. analis population. Consequently, the tested plant materials should be given due consideration for effective gram protection as a component of integrated pest management approach in storage.